La inscripción: 30 años después. ¿Quién podrá defenderla? - Ortiz Pasco, Jorge (Pontificia Universidad Católica del Perú, 2014)
One of the most important figures of Registry Law is the inscription: The reason for theregistration procedure. It seeks, through it,to grant legal protection to the owner of the registration, by the registration publicity itbrings.In this article, the author analyzes thisimportant legal figure, by focusing on the article 2013 of the Peruvian Civil Code, whichhe considers must be renovated and updated, according to the circumstances and recent regulatory changes.

Una de las figuras más importantes del Derecho Registral es la inscripción: La razón del procedimiento registral. Se busca, a través de ella, conceder protección jurídica al titular dela inscripción, valiéndose de la publicidad registral que ésta otorga.En el presente artículo, el autor realiza un análisis de esta importante figura legal, centrándose para ello en el artículo 2013 del Código Civil del Perú, el cual considera debe ser reformado y actualizado acorde a las circunstancias y modificaciones normativas  de los últimos años.
The inscription: thirty years after. Who will be able to defend it?
Keywords: Law; Inscription; Public Registers; Civil Code; Legal Certainty; Inscripción; Registros públicos; Código civil; Seguridad jurídica; https://purl.org/pe-repo/ocde/ford#5.05.01